2022
DOI: 10.1044/2022_aja-21-00247
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Technology and Infrastructure Needs in the Delivery of Virtual Hearing Aid Services

Abstract: Purpose: The digital health revolution has brought forward integral technological advancements enabling virtual care as a readily accessible delivery model. Despite this forward momentum, the field of audiology still faces barriers that impede the uptake of virtual services into routine clinical practice. The aim of this study was to gather, synthesize, and summarize the literature around virtual hearing aid intervention studies and the related technology and infrastructure requirements. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…While there is clear evidence that teleaudiological methods have been validated, there is no clear answer as to whether teleaudiology should be considered as a complement or auxiliary part of clinical audiological best practice. Infrastructure constraints have been recognized as an important factor that will determine possible and appropriate teleaudiology use [ 51 , 52 ]. In addition to practical needs, clinician preferences that will influence adoption and use of teleaudiology have been identified, which may act as a barrier of access for clients who are offered teleaudiology as part of their hearing care [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there is clear evidence that teleaudiological methods have been validated, there is no clear answer as to whether teleaudiology should be considered as a complement or auxiliary part of clinical audiological best practice. Infrastructure constraints have been recognized as an important factor that will determine possible and appropriate teleaudiology use [ 51 , 52 ]. In addition to practical needs, clinician preferences that will influence adoption and use of teleaudiology have been identified, which may act as a barrier of access for clients who are offered teleaudiology as part of their hearing care [ 51 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Australian Audiology standards do not recognize culture in the same context, instead emphasizing professional safety, learning, and behavior across three of the six domains listed [ 25 ]. Despite repeated evidence of clinical efficacy, the use and adoption of teleaudiology in audiological care has been clearly documented as being limited by clinician attitudes and reluctance [ 50 , 51 , 52 , 53 , 54 ]. This review revealed a small number of studies describing the application of teleaudiology in intervention.…”
Section: Discussionmentioning
confidence: 99%
“…As a preliminary step, the co-creation team met virtually to determine the scope of literature reviews needed. Two systematic searches contributed to the development of the CPG: (1) a systematic scoping review of technology and infrastructure needs in the delivery of virtual hearing aid services, 10 and (2) a rapid review of evidencebased documents specific to virtual audiology care (described below).…”
Section: Literature Reviewsmentioning
confidence: 99%
“…In brief, the systematic scoping review, completed in August 2020, summarised and synthesised peer-reviewed literature describing virtual hearing aid services delivered as part of intervention studies to offer evidence around the integral components and implementation factors that contribute to virtual hearing aid service delivery. 10…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation